PRODUCTION AND UTILIZATION STRATEGIES OF ORGANIC FERTILIZERS FOR ORGANIC FARMING: AN ECO-FRIENDLY APPROACH: Life Science-Botany - SHAIKH, MD.SADIQUE; A. PATIL, MADHURI (International Journal of Life Science and Pharma Research, 2013)
Todays world already suffering with lot of newer and newer problems related to water, petroleum’s, climate change, CHG and Global Warming, air pollution, water pollution, carbon and toxic gases emission, foods and grains, energy secrecy and so on. And with inclusion in those “ Soil pollution due artificial chemical fertilizers” which may increase crops, seeds & nuts, fruits, flowers, grains, cotton production, but in each farming attempt damaged soil in percent and responsible to change agricultural area into “non agricultural area”.Hence one of the excellent practices is need to find out new strategies of “production and utilization of organic fertilizers for organic farming” .Fertilizer products supplement the nutrients already in the soil. Man-made (non-organic) fertilizers are concentrated and quick acting. Organic fertilizers release nutrients slowly and usually contain many trace elements your plants need that are not found in most chemical formulations. Not all organic fertilizers are useful to plants immediately. The soil must be warm enough for organic fertilizers to break down and nutrients to be released. For a quick response, try fish emulsion or seaweed extracts. These are water soluble and instantly available to plants. For early season feeding use foliar sprays. Too much fertilizer can burn plants and leach into the groundwater, causing pollution problems. Organic fertilizers are safer to use because they are not as concentrated as chemical fertilizers. This paper we prepared with the intention to permute organic fertilizers for organic farming and to save agriculture land for long time[1,3,7]